2023
DOI: 10.1186/s13034-023-00615-w
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors associated with mental health status in an Italian sample of students during the fourth wave of COVID-19 pandemic

Mariangela Lanfredi,
Jessica Dagani,
Andrea Geviti
et al.

Abstract: Background It is well known that the COVID-19 pandemic has caused a global health crisis, especially for young people. However, most studies were conducted during the first waves of the pandemic. Few Italian studies specifically attempted to broadly assess young people’s mental health status during the fourth wave of the pandemic. Methods This study aimed at evaluating the mental health status among a group of Italian adolescents and young adults d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 85 publications
(122 reference statements)
1
2
0
Order By: Relevance
“…Interestingly, in line with previously cited studies on the Italian population [18][19][20][21][22][23], we found no changes in AD use comparable to young adults in other age groups, supporting the hypothesis that this subgroup of individuals had needed medication to treat their psychological distress during the lockdown periods and/or after the reopening phase. This evidence supports the association between younger age and lower levels of mental health during the COVID-19 pandemic [24][25][26][27][28][29][30][31][32][33][34][35][36]. We can also speculate that the increase in the use of ADs by young adults in the ASL TO4 Regione Piemonte may be related to prescriptions for the treatment of post-COVID-19 depression.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Interestingly, in line with previously cited studies on the Italian population [18][19][20][21][22][23], we found no changes in AD use comparable to young adults in other age groups, supporting the hypothesis that this subgroup of individuals had needed medication to treat their psychological distress during the lockdown periods and/or after the reopening phase. This evidence supports the association between younger age and lower levels of mental health during the COVID-19 pandemic [24][25][26][27][28][29][30][31][32][33][34][35][36]. We can also speculate that the increase in the use of ADs by young adults in the ASL TO4 Regione Piemonte may be related to prescriptions for the treatment of post-COVID-19 depression.…”
Section: Discussionsupporting
confidence: 80%
“…In this respect, the association between younger age and lower levels of mental health during the COVID-19 pandemic has been documented. In particular, young adults have been found to experience high rates of loneliness, anxious and depressive symptoms, stress, and sleep disturbances [24][25][26][27][28][29][30][31][32][33][34][35][36]. Whether these changes were associated with a parallel change in AD consumption needs to be better understood.…”
Section: Introductionmentioning
confidence: 99%
“…Gender has emerged as the most important factor in predicting mental health problems in adolescents. Females were more affected across all outcome variables, and increasing age was a significant factor for all outcomes in the female subgroup [ 69 , 70 , 71 , 72 ]. Age, however, was not a significant predictor of anxiety symptoms in boys.…”
Section: Discussionmentioning
confidence: 99%